Early response and local control of stage I non‐small‐cell lung cancer after stereotactic radiotherapy: difference by histology - Miyakawa, Akifumi (Cancer Sci, 2012)
To investigate the possible influences of various factors on tumor response to radiation, regression speeds and long‐term local control rates of primary adenocarcinoma and squamous cell carcinoma of the lung after stereotactic body radiotherapy were evaluated. Ninety‐one patients (65 men and 26 women) with a median age of 76 years were serially examined using computed tomography at 2, 4 and 6 months after treatment. Tumor histology was adenocarcinoma in 62 patients and squamous cell carcinoma in 29 patients. The prescribed dose was 48 Gy in four fractions given twice a week for T1 tumors (≤3 cm) and 52 Gy in four fractions given twice a week for T2 tumors (3–5 cm). Tumor shrinkage speed and 3‐year local control rates were similar between T1 and T2 tumors and between patients with normal pulmonary function and those with impaired function. Squamous cell carcinomas shrank faster than adenocarcinomas at 2 and 4 months after radiation, but mean relative tumor size at 6 months and local control rates at 3 years did not differ significantly between the two histologies. Tumors in patients with a higher hemoglobin level tended to shrink faster but the control rates were not different. It is concluded that, although squamous cell carcinoma shrinks faster than adenocarcinoma, the two types of lung cancer are of similar radiosensitivity in terms of long‐term control rates. Radiosensitivity should not be evaluated by early tumor response. (Cancer Sci 2013; 104: 130–134)